Pengaruh Kualitas Audit, Laporan Manajerial, dan Komite Audit Terhadap Kualitas Pelaporan Keuangan Perusahaan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Laksono, Dwi Aryo Prasetyo; Musfitria, Anessa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The real estate sector in Indonesia has experienced rapid growth in recent years. This sector also has to face various challenges such as economic uncertainty, regulatory changes, and increasingly fierce competition. The purpose of this study is to analyze whether audit quality, managerial reports, and audit committees affect the quality of financial reporting of real estate companies listed on the Indonesia Stock Exchange in 2021-2023. The data in this study used secondary data with the sampling method using the judgment sampling method, which is one type of purposive sampling. The data analysis method uses descriptive statistics, classical assumption tests, multiple linear regression and hypothesis testing. Based on the results of the study, it shows that the coefficient of determination is 19.6%, which means that the audit quality variables, managerial reports and audit committees have the ability to influence the quality of financial reporting, while the remaining 80.4% is influenced by other variables. The results of the F test show the value of f count 4.172 f table 2.874 and a significance level of 0.012 0.05, it can be concluded that the variables of audit quality, managerial reports, and audit committees simultaneously have a positive effect on the quality of financial reporting. The T test results show that the audit quality obtained a t count value of 2.081 t table 1.688 and a significance level of 0.045 0.05, the managerial report obtained a t count of 2.347 t table 1.688 and a significance level of 0.025 0.05, the audit committee obtained a t count of 2.571 t table 1.688 and a significance level of 0.014 0.05. Then the three variables, namely audit quality, managerial reports, and audit committees partially have a positive effect on the quality of financial reporting.